Change in the Physiological Aspects of Soybean Caused by Infestation by Bemisia tabaci MEAM1 - Silva, Luciana B.; Almeida, Lucas C.; e Silva, Maria C. F.; Brito, Ramilos R. de; Miranda, Rafael de S.; Rodrigues, Raimundo H. F.; Santos, Carlos M. P. dos; Ribeiro, Gilvana da S.; Morais, João V. S.; Silva, Alisson F. T. da; Mayard, Hernesise; Oliveira, Thayline Rodrigues de; et al. (MDPI, 2024)
Whiteflies cause significant crop losses through direct sap feeding, inducing plant physiological disorders and promoting the growth of sooty mold. Moreover, whiteflies can indirectly harm plants by transmitting plant viruses, particularly begomoviruses and criniviruses, resulting in severe viral disease epidemics. This study aimed to evaluate the physiological characteristics of susceptible and resistant soybean cultivars to B. tabaci. The experiments were conducted in a greenhouse. Eleven soybean cultivars were selected and infested with 100 adults of B. tabaci at the V3 stage. The evaluation of photosynthetic parameters, such as photosynthetic rate, leaf transpiration, stomatal conductance, and internal CO2 concentration, revealed that B. tabaci infestation influenced gas exchange in soybean plants. The photosynthetic rate was higher in cultivars AS3810 and M8349 during the V6 stage. Infestations caused alterations in photosynthetic parameters, suggesting increased energy demand to maintain photosynthetic activity. However, the response to infestation varied among the different cultivars, indicating varying levels of resistance and tolerance to the whitefly’s damage. Furthermore, the infestation had a more notable impact during the vegetative phenological stage. In summary, infestation by B. tabaci has a discernible impact on the physiology of soybean plants, resulting in alterations in gas exchange parameters and water use efficiency. The reaction to infestation exhibited variations among different soybean cultivars, indicating potential differences in resistance to the pest. This study underscores the significance of assessing the physiological consequences of whitefly infestations on soybean crops.
Keywords: gas exchange; Glycine max; insect pest; photosynthetic parameters; plants resistance; whitefly